Distinct Subgroups of Cicer echinospermum Are Associated with Hybrid Sterility and Breakdown in Interspecific Crosses with Cultivated Chickpea. Issue 6 (14th September 2017) - Kahraman, Abdullah; Pandey, Anamika; Khan, Mohd Kamran; Lindsay, Donna; Moenga, Susan; Vance, Lisa; Bergmann, Emily; Carrasquilla‐Garcia, Noelia; Shin, Min‐Gyoung; Chang, Peter L.; von Wettberg, Eric J. B.; Tar'an, Bunyamin; et al.
Abstract : Crop wild relatives are a reservoir of phenotypic variation not present in the germplasm of cultivated species and thus have great potential for crop improvement. However, issues of genetic compatibility often interfere with effective utilization of crop wild relative taxa. Among chickpea ( Cicer arietinum L.) crop wild relatives, Cicer echinospermum P.H. Davis is the sole species in the secondary genepool, being partially compatible with the primary genepool that is composed of the cultigen and its progenitor wild species Cicer reticulatum Ladizinksy. We report results from genetic studies among interspecific hybrids between cultivated chickpea and accessions from six recently identified wild C. echinospermum sites in southeastern Turkey, encompassing the known genetic diversity of the secondary genepool. Our studies indicate that both hybrid sterility and hybrid breakdown occur and are associated with distinct subgroups of C. echinospermum . Analysis of early‐generation progenies suggests that both hybrid sterility and hybrid breakdown are conditioned by one to few genetic loci. These results clarify ambiguity in the nature of the hybridization barriers of reduced fertility in interspecific crossing of cultivated chickpea with C. echinospermum and should foster a more systematic and wider use of C. echinospermum for base broadening of cultivated chickpea.